Distinct characteristics of BTLA/HVEM axis expression on Tregs and its impact on the expansion and attributes of Tregs in patients with active pulmonary tuberculosis - Peijun Tang; Peijun Tang; Xinghua Shen; Jianling Gao; Jianping Zhang; Yanjun Feng; Ji Zhang; Ziyi Huang; Ziyi Huang; Ziyi Huang; Xuefeng Wang (Frontiers in Cellular and Infection Microbiology)
IntroductionPulmonary tuberculosis (PTB) remains one of the deadliest infectious diseases. Understanding PTB immunity is of potential value for exploring immunotherapy for treating chemotherapy-resistant PTB. CD4+CD25+Foxp3+ regulatory T cells (Tregs) are key players that impair immune responses to Mycobacteria tuberculosis (MTB). Currently, the intrinsic factors governing Treg expansion and influencing the immunosuppressive attributes of Tregs in PTB patients are far from clear.MethodsHere, we employed flow cytometry to determine the frequency of Tregs and the expression of B and T lymphocyte attenuator (BTLA) and its ligand, herpesvirus entry mediator (HVEM), on Tregs in patients with active PTB. Furthermore, the expression of conventional T cells and of programmed death-ligand 1 (PD-L1) and programmed death-1 (PD-1) on Tregs in patients with active PTB was determined. We then examined the characteristics of BTLA/HVEM expression and its correlation with Treg frequency and PD-L1 and PD-1 expression on Tregs in PTB patients.ResultsThe frequency of Tregs was increased in PTB patients and it had a relevance to PTB progression. Intriguingly, the axis of cosignal molecules, BTLA and HVEM, were both downregulated on the Tregs of PTB patients compared with healthy controls (HCs), which was the opposite of their upregulation on conventional T cells. Unexpectedly, their expression levels were positively correlated with the frequency of Tregs, respectively. These seemingly contradictory results may be interpreted as follows: the downregulation of BTLA and HVEM may alleviate BTLA/HVEM cis-interaction-mediated coinhibitory signals pressing on naïve Tregs, helping their activation, while the BTLA/HVEM axis on effector Tregs induces a costimulatory signal, promoting their expansion. Certainly, the mechanism underlying such complex effects remains to be explored. Additionally, PD-L1 and PD-1, regarded as two of the markers characterizing the immunosuppressive attributes and differentiation potential of Tregs, were upregulated on the Tregs of PTB patients. Further analysis revealed that the expression levels of BTLA and HVEM were positively correlated with the frequency of PD-1+Tregs and PD-L1+Tregs, respectively.ConclusionOur study illuminated distinct characteristics of BTLA/HVEM axis expression on Tregs and uncovered its impact on the expansion and attributes of Tregs in patients with active PTB. Therefore, blockade of the BTLA/HVEM axis may be a promising potential pathway to reduce Treg expansion for the improvement of anti-MTB immune responses.